ANALISIS FAKTOR YANG MEMPENGARUHI NON MUSLIM MENJADI NASABAH BANK SYARIAH INDONESIA DI MEDAN - Anjur Perkasa Alam, Jureid Lubis (Islamic Circle, 2021)
The purpose of this study is to find out how the influence of facilities, promotions and products of Islamic Bank Indonesia affects non-Muslims to become customers. The sampling method used by the researcher is Non Probability Sampling, which is a technique where every member of the sample in the population has the same opportunity to become a member of the sample. An example of a purposive sampling technique (Judgement Sampling) is a sampling technique based on an assessment of the characteristics of the sample members that is adjusted to the researcher's goals. Based on the research results, the most powerful factors influencing non-Muslims to become customers at Bank Syariah Indonesia are promotions, products and facilities. The first strong influence is promotion with a significance of 0.371, both products 0.528 have a strong influence and the last 0.467 facilities have that influence